Autism Spectrum Disorder: The applicability of IEP in schools - Silva, Juçara Aguiar Guimarães; Aguiar, Naiara Bonfim; Braga, Jefferson da Silva Macedo; Martins, Antônio Carlos Toledo; Lopes, Eliane Pereira; Oliveira, Jaquelina Aparecida de; Silva, Talita Neves; Passos, Luiz Marcelo; Cruz, Mona Liza Silva; Rodrigues, Elanir Menezes (Seven Editora, 2024)
This article addresses the importance of implementing the Individualized Educational Plan (IEP) for students with Autism Spectrum Disorder (ASD) in school environments. The PEI is a personalized document that describes the specific educational needs of a student with ASD and the services that the school will provide to meet these needs, seeking to address the effective development of an IEP for students with ASD, taking into account their difficulties and potential . Strategies for comprehensive assessment, setting realistic and measurable goals, adapting the learning environment, implementing specialized teaching techniques, and collaborating with specialized professionals are covered. Furthermore, the article highlights the importance of a student-centered approach, which values their individual abilities and promotes their full development, taking into account their specific needs and the diversity of the autism spectrum. The inclusion of activities of interest and motivation, family involvement and promotion of awareness are important aspects to ensure the effectiveness of the PEI. Through case studies, scientific evidence and practical experiences, the article highlights the benefits of using IEP for students with ASD, while exploring challenges and possible solutions for its effective implementation. The need for a flexible, student-centered approach committed to promoting educational success and student well-being in the school environment is highlighted. DOI:https://doi.org/10.56238/sevened2024.007-017